The Isomorphism Theorem of Regular Bisimple $ω^2$-Semigroups (Communications in Mathematical Research, 2021)
In this paper we study the isomorphisms of two regular bisimple $ω^2$-semigroups and obtain a criterion for two such semigroups to be isomorphic.
Keywords: regular $ω^2$-semigroup; generalized Bruck-Reilly extension; isomorphism.